THE EVOLUTION OF CONTENT MARKETING IN THE DIGITAL AGE: FROM SEO TO STORYTELLING - Henny Noviany; Oggy Akmadani (CV. Adiba Aisha Amira, 2024)
This research examines the evolution of content marketing in the digital age, tracing its journey from an initial focus on search engine optimization (SEO) to a more complex storytelling approach. The method of this study is literature. The results show a significant shift from keyword-based strategies to a more audience- centric approach, with an emphasis on content quality and engagement. The use of data analytics and new technologies such as artificial intelligence (AI) were also identified as key factors in the personalization and effectiveness of content marketing.